Reducing the evaporation of stored Iraqi crude oil - R. rassoul, G. A.; hameed khlaif, Tahseen (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
In order to reduce the losses due to evaporation in the stored crude oil and minimizing the decrease in °API many affecting parameters were studied (i.e. Different storage system, namely batch system with different types of storage tanks under different temperatures and:or different pressures). Continuous circulation storage system was also studied. It was found that increasing pressure of the inert gas from 1 bar to 8 bar over the surface of the crude oil will decrease the percentage losses due to evaporation by (0.016%) and decrease the change of °API by (0.9) during 96 hours storage time. Similarly using covering by surfactant (potassium oleate) or using polymer (polyurethane foam) decreases the percentage evaporation losses compared with uncovered surface of the blend crude oil. In each surfactants and polymers the layer thickness was (1.0, 1.5, 2.0, 2.5, 3.0 cm), and increasing the thickness of the surfactant to 2.5 cm or of the polymer to 3 cm was found to be best required thickness. Surfactant gave lower percentage evaporation losses than polymer, for fixed roof tank (i.e. 0.299%, 0.383%) for 120 hours evaporation time. Different processed storage tanks namely (fixed roof, external moving roof, fixed and internal moving) were studied and fixed and moving roof was the best in reducing evaporation losses (0.453%) for 120 hours. In continuous circulation for proposed continuous storage system, the percentage evaporation losses for covered with surfactant, covered with polymer, and uncovered surface of blend crude oil were (0.328%), (0.378%), and (0.45%) respectively at 24 °C for 96 hours evaporation time.